Effectiveness of the Schroth Method in Reducing Cobb Angle and Improving Quality of Life in Adolescents With Idiopathic Scoliosis - Menaria, Deepansha; Khan, Jafar; Warsi, Rahat khan; Sharma, Deepak; Pal, Renuka; Lhar, Deepak; Jain, Preksha; Kania, Vaishnavi; Choubisa, Chitrakshi A; Menaria, Dinesh (Journal of Neonatal Surgery, 2025)
Background:Adolescent idiopathic scoliosis (AIS) is a progressive spinal deformity marked by a three-dimensional curvature of the spine, often emerging during periods of rapid growth. Conservative exercise-based interventions have gained prominence as alternatives to bracing or surgical correction. The Schroth method, a scoliosis-specific exercise approach, emphasizes postural correction, muscle symmetry, and rotational breathing techniques. Objective:To evaluate the effectiveness of the Schroth method in reducing Cobb angle, alleviating pain, and improving posture and quality of life among adolescents with idiopathic scoliosis. Methods:A total of 30 adolescents aged 10–18 years with mild to moderate AIS (Cobb angle 20°–45°) underwent a 7-week Schroth-based physiotherapy program, five sessions per week. Pre- and post-intervention assessments included Cobb angle (via radiography), Visual Analog Scale (VAS) for pain, and observational postural alignment analysis. Results:The mean pre-treatment Cobb angle was 27.17° (±6.80), which significantly decreased to 19.03° (±6.41) post-treatment (p < 0.001). VAS scores reduced from 7.03 (±1.20) to 2.67 (±1.18) (p < 0.001), indicating notable pain relief. Observational assessments confirmed improvements in trunk symmetry and postural control. Conclusion:The Schroth method is effective in reducing spinal curvature, relieving pain, and improving postural alignment in adolescents with idiopathic scoliosis. It presents a viable conservative treatment alternative to surgical and bracing options, especially in mild to moderate AIS cases